Synthesis & Characterization of Some Mixed Ligand Complexes of Pd(II), Rh(III) and Pt(IV) with Carboxylic Hydrazones as Primary and Dithiooxamide as Co-ligand - K. AGARWAL, SURESH (Asian Journal of Chemistry, 2010)
Mixed ligand complexes of Pd(II), Rh(III) and Pt(IV) with 2-acetyl pyridyl-pyrazine-carboxylic hydrozone (apph)/2-carboxaldehyde pyridyl-pyrazinecarboxylic hydroazone (cpph) as primary and dithiooxamide (dto) as co-ligand have been synthesised and characterised on the basis of analytical, conductance, spectral and thermal data. Analytical data suggested 1:1:1 (M-L/L′-L′′ Clx) Cly stoichiometric composition for the present complexes [where M = Pd(II), Rh(III) and Pt(IV), L = apph, L′ = cpph and L′′ = dto, x = 0 for Pd(II) complexes and x = 2 for Rh (III) and Pt(IV) complexes, y = 1 for Rh(III) complexes and y = 2 for Pd(II) and Pt(IV) complexes]. Electrolytic conductance data (ΔM = 180-184.4 ohm-1cm2 mol-1 for Pd(II) and Pt(IV) complexes and 120.2-124.4 ohm-1cm2 mol-1 for Rh(III) complexes revealed 1 : 2 electrolytic nature of Pd(II) and Pt(IV) complexes and 1:1 electrolytic nature of Rh(III) complexes. IR spectra confirm the bidentate nature of all the three ligands. Reflectance spectra correspond to square planar geometry of Pd(II) and octahedral geometry of Rh(III) and Pt(IV) mixed ligand complexes. The thermal decomposition study of the complexes reveals that the hydrazone moiety is lost in 400-510ºC temperatuer range. At last metallic residue is left as the ultimate product in 670-710ºC temperature range. The mixed ligand complexes were screened for their antimicrobial activity against E. coli and S. aureus. The results of screening show that the complexes are more active against E. coli in comparison to S. aureus.